Vocabulary depth as preliteracy skill - García Gómez, Lydia; Rueda Sánchez, Mercedes I. (Revista de Investigación en Logopedia, 2022)
The aim of this study is to explore the predictive value of vocabulary breadth and depth together with the classical variables of phonological awareness, naming speed and alphabetic knowledge in explaining progress in the initial learning of reading and writing in a sample of 162 students in the 3rd year of kindergarten. Early detection of risks in learning to read is essential to be able to intervene proactively if signs of dyslexia are found. The study of skills that predict successful literacy acquisition may be useful to identify risk indicators of learning disabilities in reading and writing in early childhood education. The results found confirm the contribution of classical variables and reveal that especially vocabulary depth seems to be a good predictor of success in early literacy performance. The educational implications of these findings are discussed.
Keywords: Dyslexia risks; Preliteracy skills; Prevention; Vocabulary depth